A mild and practical approach to N-CF3 secondary amines via oxidative fluorination of isocyanides - Jia-Luo Fu; Jun-Yunzi Wu; Juan-Fen Shi; Long-Ling Huang; Honggen Wang; Qingjiang Li (Nature Communications)
Abstract N-trifluoromethyl compounds, featuring a CF3 group directly attached to nitrogen, are valuable in medicinal chemistry. Despite substantial advances in their synthesis over the past decade, the efficient preparation of inherently unstable N-CF3 secondary amines remains a challenge in synthetic chemistry. Herein, we present a mild and practical method for synthesizing these compounds via oxidative fluorination of isocyanides using iodine as the oxidant, silver fluoride as the fluorinating reagent, and tert-butyldimethylsilane as the proton precursor. This approach benefits from simple workup, as all reagents and by-products can be easily removed through simple filtration and evaporation. This protocol features a broad substrate scope, good functional group tolerance, and good to excellent yields. Additionally, the resulting products can be readily converted into N-CF3 carbamoyl fluorides, valuable building blocks for the synthesis of diverse N-CF3 carbonyl derivatives.